Ferrite with high Curie temperature and high magnetic permeability and preparation method thereof
By adjusting the ratio of Fe2O3, ZnO and MnO in ferrite, introducing auxiliary materials and additives, and optimizing the sintering process, the problem of large loss of traditional ferrite at high Curie temperature is solved, and high Curie temperature and high magnetic properties are achieved. Conductivity effect, suitable for high frequency and high temperature applications.
Patent Information
- Application Number
- CN202410965719.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-18
- Publication Date
- 2025-01-17
AI Technical Summary
Traditional ferrite has a large eddy current loss and low magnetic permeability in high Curie temperature environments, which limits its application in low frequency and strong electric and high power fields.
By adjusting the ratio of Fe2O3, ZnO and MnO, and introducing auxiliary materials such as CaCO3, ZrO2, Nb2O, Co2O3, SiO2, TiO2, and the additive Ca0.85Ba0.15Cu3Ti3.97Hf0.03O12, the sintering process is optimized to increase the high Curie temperature of the material. and magnetic permeability.
It achieves low loss and high magnetic permeability of the material at high Curie temperature, is suitable for high frequency and high temperature applications, and reduces loss under 100-140°C usage conditions.
Smart Images

Figure BDA0004951716670000071 
Figure BDA0004951716670000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ferrite magnetic materials, and in particular to a high Curie temperature and high magnetic permeability ferrite and a preparation method thereof. Background Art
[0002] Ferrite is a metal oxide with ferrimagnetism. The resistivity of ferrite is much greater than that of single metal or alloy magnetic materials, and it has higher dielectric properties and magnetic permeability. Therefore, ferrite has become a widely used non-metallic magnetic material in the field of high-frequency weak electricity. Since the magnetic energy stored in ferrite per unit volume is low, the saturated magnetic induction intensity (Bs) is also low, which limits its application in the fields of low-frequency strong electricity and high power that require higher magnetic energy density.
[0003] With the rapid development of electronic technology, the application fields of electronic systems are becoming more and more extensive, the types of electronic equipment are increasing, and the connection between electronic equipment and people's work and life is becoming increasingly close. Miniaturization, lightweight, and integration are irreversible trends in the development of modern electronic products, which makes the demand for products develop in the direction of high Curie temperature, low loss, and high magnetic permeability. Although traditional manganese-zinc ferrite has a low resistivity, its eddy current loss is large in a high Curie temperature environment, and its advantages are not obvious. Therefore, it has become a trend to develop a ferrite magnetic material with high Curie temperature and high magnetic permeability. Summary of the invention
[0004] The purpose of this application is to provide a high Curie temperature and high magnetic permeability ferrite and a preparation method thereof in view of the deficiencies of the current technology.
[0005] In the first aspect, the present application provides a high Curie temperature and high magnetic permeability ferrite, which adopts the following technical solution: A high Curie temperature and high magnetic permeability ferrite comprises a main component, auxiliary materials and an additive. The main component is composed of Fe2O3, ZnO and MnO in molar fraction, with a content of Fe2O3 of 52-53mol%, ZnO of 1819mol%, and the rest of MnO. The auxiliary materials comprise CaCO3, ZrO2, Nb2O, Co2O3, SiO2 and TiO2. The auxiliary materials are calculated based on the total weight of the main component, and the content of each auxiliary material component is: CaCO3 0.05-0.07wt%, ZrO2 0.001-0.005wt%, Nb2O 0.025-0.04wt%, Co2O3 0.26-0.28wt%, SiO2 0.004-0.007wt%, TiO2 0.003-0.005wt%. The additive is CaCO3. 0.85 Ba 0.15 Cu3Ti 3.97 Hf 0.03 O 12The auxiliary agent has a content of 0.05-0.08wt% based on the total weight of the main components.
[0006] By adopting the above technical scheme, in the high Curie temperature and high magnetic permeability ferrite of the present application, the main components Fe2O3, ZnO and MnO play the basic magnetic and magnetic permeability properties. Fe2O3 is the main magnetic material, and ZnO and MnO are the components for adjusting the magnetic permeability and Curie temperature. The addition of auxiliary materials can further optimize the material properties. CaCO3 is a sintering aid, which helps to improve crystal growth and magnetic properties. ZrO2 and Nb2O5 play a role in inhibiting crystal growth and uniform dispersion, and can optimize the microstructure of the material. Co2O3 is beneficial to improving the magnetic properties and magnetic permeability of the material. SiO2 and TiO2 are impurities that inhibit crystal growth and reduce hysteresis. Auxiliary agent Ca 0.85 Ba 0.15 Cu3Ti 3.97 Hf 0.03 O 12 The addition of can improve the dielectric properties of the material. The Ba element can promote the growth of grains and increase the dielectric constant. The incorporation of the Hf element can inhibit grain growth, causing the dielectric constant of the sample to decrease, but at the same time reducing the loss. The synergistic effect of the components can improve the overall performance of the material. Adjusting the ratio of the main components can give the material a high Curie temperature and high magnetic permeability. The addition of auxiliary materials and the doping of auxiliaries can optimize the crystal growth, dispersibility and dielectric properties of the material. By optimizing the sintering process, the high Curie temperature and high magnetic permeability ferrite of the present application has the effect of high Curie temperature and high magnetic permeability, which effectively reduces the loss under the use conditions of 100-140°C by adjusting the ratio of raw materials and optimizing the sintering process.
[0007] Preferably, the preparation method of the auxiliary agent is: copper nitrate trihydrate, calcium nitrate tetrahydrate, tetrabutyl titanate, nitrocitrate, barium nitrate and hafnium nitrate are weighed according to the stoichiometric ratio and dissolved in anhydrous ethanol to obtain a mixed solution, which is kept warm at 83°C for 1.8 hours, and after adjusting the pH, the mixture is kept warm for reaction until a sol is formed, and then dried, fired and ground to obtain an auxiliary agent powder, wherein the particle size of the auxiliary agent powder is between 0.9-1.1 μm.
[0008] By adopting the above-mentioned technical scheme, the less doping amount of the additive prepared in the present application can make the Ba and Hf elements enter the crystal lattice, avoiding the precipitation of other impurities, and the radius of the doped elements is similar to the original Ca and Ti radius, so they can enter the crystal lattice to form a continuous solid solution. Ba will promote the growth of sample grains. The incorporation of Ba can effectively increase the dielectric constant, while the incorporation of Hf will inhibit grain growth, thereby reducing the dielectric constant of the sample and reducing the loss.
[0009] In a second aspect, the present application provides a method for preparing a high Curie temperature and high permeability ferrite, using the following technical solution: A method for preparing a high Curie temperature and high magnetic permeability ferrite, using the above-mentioned high Curie temperature and high magnetic permeability ferrite raw material, comprises the following steps: S31, mixing the main components Fe2O3, ZnO and MnO according to the formula, and then mixing with water in a ratio of 1:1.5-2.0, sand grinding and drying for 2-3 hours, and then pre-calcining at a temperature of 800-850° C. for 1-2 hours in an air atmosphere to obtain a pre-calcined material; S32, mixing auxiliary materials, additives and the pre-burned material obtained in step S31, performing secondary sand grinding and drying to obtain sand-milled powder; S33, the sand-milled powder in step S32 is successively screened through an 80-mesh screen, spray granulated, molded and sintered to obtain a ferrite with high Curie temperature and high magnetic permeability; the molding in step S33 includes making the product obtained after granulation into a sample ring blank; the sintering process in step S33 includes: heating the sample ring blank to a first temperature, introducing a certain amount of oxygen during the first insulation, cooling to a second temperature at a first cooling rate under a balanced oxygen partial pressure atmosphere, second insulation, and finally cooling to a third temperature at a second cooling rate; the first temperature is 1000-1100°C; the second temperature is 270-300°C; the third temperature is 55-65°C.
[0010] Preferably, in step S32, the secondary sand grinding time is 2-3 hours; and the particle size D50 of the sand grinding powder is 0.8-1.0 μm.
[0011] Preferably, in step S33, a binder is added during the spray granulation process, and the binder is a composition of polyvinyl alcohol and zinc stearate in a mass ratio of 8:1-2.
[0012] Preferably, the concentration of the binder solution is 5-10wt%, and the binder is 6-10% of the sieved sand-ground powder.
[0013] Preferably, in step S33, the heating rate of the heating is 2-3°C / min, and the insulation time at the first temperature is 4-6h.
[0014] Preferably, in step S33, the first cooling rate is 3.5-4.5°C / min, and the second temperature holding time is 3-5h.
[0015] Preferably, in step S33, the second cooling rate is 0.2-0.4°C / min.
[0016] Preferably, in step S33, the oxygen content in the equilibrium oxygen partial pressure atmosphere is 2.1-2.5 vol%.
[0017] By adopting the above technical scheme, in the method for preparing high Curie temperature and high magnetic permeability ferrite, the role and synergistic effect of each step are as follows: Step S31: In this step, the main components Fe2O3, ZnO and MnO are mixed with water and sand-milled and dried for pre-sintering. The main purpose is to make the raw materials uniformly mixed and form pre-sintered materials through sand-milling and pre-sintering treatment, which is conducive to the molding and sintering of the subsequent steps. Pre-sintering also helps to remove some volatile substances and improve the crystal structure of the material. Step S32: In this step, the mixed pre-sintered materials are sand-milled and dried with auxiliary materials and additives to finally obtain sand-milled powder. The role of this step is to mix the pre-sintered materials with auxiliary materials and additives more evenly, so that they have better reactivity and plasticity in the subsequent molding and sintering processes. Step S33: In this step, the sand-milled powder is screened, spray granulated, molded and sintered, and finally prepares high Curie temperature and high magnetic permeability ferrite. The purpose of screening is to remove the uneven particles in the powder to make its particle size more uniform. Spray granulation helps improve the fluidity and molding performance of the powder. In the molding stage, the powder is made into a sample ring blank to give it a specific shape and structure. The sintering process controls the sintering temperature and cooling rate through a special cooling curve, which helps to control the grain size and stabilize the material structure, thereby achieving the effect of high Curie temperature and high magnetic permeability. The synergy between the various steps is to optimize the material ratio and process so that the material has better physical properties. By adjusting the raw material ratio and mixing process, the uniform distribution of material components can be achieved. Pre-sintering and sand grinding can improve the reactivity and plasticity of the material. The preparation and molding process of sand-ground powder can optimize the structure and shape of the material. The final sintering process controls the grain size and structure through a special cooling curve, so that the material has a high Curie temperature and high magnetic permeability. The adjustment of the doping amount of the additive can enable the Ba and Hf elements to enter the lattice and form a continuous solid solution, thereby increasing the dielectric constant.
[0018] In summary, the beneficial technical effects of this application are: 1. By adjusting the ratio of raw materials and optimizing the sintering process, the loss under the use condition of 100-140℃ is effectively reduced. This means that the material has better stability and reliability in high temperature environment.
[0019] 2. It has the effects of high Curie temperature and high magnetic permeability. High Curie temperature means that the material can still maintain high magnetic properties at high temperatures, while high magnetic permeability means that the material has better electrical conductivity under high frequency conditions.
[0020] 3. Through the combination of low-temperature sintering process and special cooling curve, the grain size of the material can be controlled. Small grain size helps to reduce the high temperature sensitivity and high temperature loss of the material, and improve the stability and performance of the material.
[0021] 4. The small amount of additive doping allows Ba and Hf elements to enter the crystal lattice, avoiding the precipitation of other impurities. By making the radius of the doped element close to the radius of the original element, a continuous solid solution is formed. The incorporation of Ba promotes the growth of grains and increases the dielectric constant, while the incorporation of Hf inhibits grain growth and reduces losses. DETAILED DESCRIPTION
[0022] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0023] Example 1 A high Curie temperature and high magnetic permeability ferrite comprises a main component, auxiliary materials and an additive. The main component, measured by mole fraction, consists of Fe2O3, ZnO and MnO, with a content of Fe2O3 52mol%, ZnO 18mol%, and the rest being MnO; the auxiliary materials comprise CaCO3, ZrO2, Nb2O, Co2O3, SiO2 and TiO2; the auxiliary materials, measured by the total weight of the main component, have a content of CaCO3 0.05wt%, ZrO2 0.001wt%, Nb2O 0.025wt%, Co2O3 0.26wt%, SiO2 0.004wt%, and TiO2 0.003wt%; the additive is CaCO3, ZrO2, Nb2O, Co2O3, SiO2, and TiO2. 0.85 Ba 0.15 Cu3Ti 3.97 Hf 0.03 O 12 The content of the auxiliary agent is 0.05wt% based on the total weight of the main components. The preparation method of the auxiliary agent is as follows: 3 mol of copper nitrate trihydrate, 0.85 mol of calcium nitrate tetrahydrate, 3.97 mol of tetrabutyl titanate, 0.3 mol of nitrocitric acid, 0.15 mol of barium nitrate and 0.03 mol of hafnium nitrate are weighed and dissolved in 20L of anhydrous ethanol according to the stoichiometric ratio to obtain a mixed solution, which is kept at 83°C for 1.8 hours, and after adjusting the pH, the mixture is kept warm for reaction until a sol is formed, and then dried, fired and ground to obtain an auxiliary agent powder, wherein the particle size of the auxiliary agent powder is between 0.9 and 1.1 μm.
[0024] A method for preparing a high Curie temperature and high magnetic permeability ferrite, using the above-mentioned high Curie temperature and high magnetic permeability ferrite raw material, comprises the following steps: S31, mixing the main components Fe2O3, ZnO and MnO according to the formula, and then mixing with water in a ratio of 1:1.5, sand grinding and drying for 2 hours, and then pre-calcining at a temperature of 800° C. for 2 hours in an air atmosphere to obtain a pre-calcined material; S32, mixing auxiliary materials, additives and the pre-burned material obtained in step S31, performing secondary sand grinding and drying to obtain sand-milled powder, the secondary sand grinding time is 2 hours; the particle size D50 of the sand-milled powder is 0.8-1.0 μm; S33, the sand-milled powder of step S32 is successively sieved through an 80-mesh sieve, spray-granulated, and a binder is added during the spray-granulation process, wherein the binder is a composition of polyvinyl alcohol and zinc stearate in a mass ratio of 8:1, the binder solution concentration is 5wt%, and the binder is 10% of the powder after the sand-milled powder is sieved; forming into a sample ring blank and sintering to obtain a high Curie temperature and high permeability ferrite; the sintering process comprises: heating the sample ring blank to a first temperature of 1000°C at a heating rate of 2°C / min, a first insulation time of 6h, introducing a certain amount of oxygen during insulation, under a balanced oxygen partial pressure atmosphere, the oxygen content in the balanced oxygen partial pressure atmosphere is 2.1vol%, cooling to a second temperature of 270°C at a first cooling rate of 3.5°C / min, a second insulation time of 3h, and finally cooling to a third temperature of 55°C at a second cooling rate of 0.2°C / min.
[0025] Example 2 A high Curie temperature and high magnetic permeability ferrite comprises a main component, auxiliary materials and an additive. The main component, measured by mole fraction, consists of Fe2O3, ZnO and MnO, with a content of Fe2O3 53mol%, ZnO 19mol%, and the rest being MnO; the auxiliary materials comprise CaCO3, ZrO2, Nb2O, Co2O3, SiO2, and TiO2; the auxiliary materials, measured by the total weight of the main component, have a content of CaCO3 0.05wt%, ZrO2 0.005wt%, Nb2O 0.04wt%, Co2O3 0.28wt%, SiO2 0.007wt%, and TiO2 0.005wt%; the additive is CaCO3, ZrO2, Nb2O, Co2O3, SiO2, and TiO2. 0.85 Ba 0.15 Cu3Ti 3.97 Hf 0.03 O 12The auxiliary material is calculated based on the total weight of the main components, and its content is 0.08wt%. The preparation method of the auxiliary agent is as follows: according to the stoichiometric ratio, 3 mol of copper nitrate trihydrate, 0.85 mol of calcium nitrate tetrahydrate, 3.97 mol of tetrabutyl titanate, 0.3 mol of nitrocitric acid, 0.15 mol of barium nitrate and 0.03 mol of hafnium nitrate are weighed and dissolved in 20L of anhydrous ethanol to obtain a mixed solution, which is kept at 83°C for 1.8 hours, and after adjusting the pH, the mixture is kept warm for reaction until a sol is formed, and then dried, fired and ground to obtain an auxiliary powder, wherein the particle size of the auxiliary powder is between 0.9-1.1μm.
[0026] A method for preparing a high Curie temperature and high magnetic permeability ferrite, using the above-mentioned high Curie temperature and high magnetic permeability ferrite raw material, comprises the following steps: S31, mixing the main components Fe2O3, ZnO and MnO according to the formula, and then mixing with water in a ratio of 1:2.0, sand grinding and drying for 3 hours, and then pre-calcining at a temperature of 850° C. for 1 hour in an air atmosphere to obtain a pre-calcined material; S32, mixing auxiliary materials, additives and the pre-burned material obtained in step S31, performing secondary sand grinding and drying to obtain sand-milled powder, the secondary sand grinding time is 3 hours; the particle size D50 of the sand-milled powder is 0.8-1.0 μm; S33, the sand-milled powder of step S32 is successively sieved through an 80-mesh sieve, spray-granulated, and a binder is added during the spray-granulation process, wherein the binder is a composition of polyvinyl alcohol and zinc stearate in a mass ratio of 8:2, the binder solution concentration is 10wt%, and the binder is 6% of the powder after the sand-milled powder is sieved; forming into a sample ring blank and sintering to obtain a high Curie temperature and high permeability ferrite; the sintering process comprises: heating the sample ring blank to a first temperature of 1100°C at a heating rate of 3°C / min, a first insulation time of 6h, introducing a certain amount of oxygen during insulation, under a balanced oxygen partial pressure atmosphere, the oxygen content in the balanced oxygen partial pressure atmosphere is 2.5vol%, cooling to a second temperature of 300°C at a first cooling rate of 4.5°C / min, a second insulation time of 5h, and finally cooling to a third temperature of 65°C at a second cooling rate of 0.4°C / min.
[0027] Example 3 A high Curie temperature and high magnetic permeability ferrite comprises a main component, auxiliary materials and an additive. The main component, measured by mole fraction, consists of Fe2O3, ZnO and MnO, with a content of Fe2O3 52.5mol%, ZnO 18.5mol%, and the rest being MnO; the auxiliary materials comprise CaCO3, ZrO2, Nb2O, Co2O3, SiO2, and TiO2; the auxiliary materials, measured by the total weight of the main component, have a content of CaCO3 0.06wt%, ZrO2 0.003wt%, Nb2O 0.033wt%, Co2O3 0.27wt%, SiO2 0.005wt%, and TiO2 0.004wt%; the additive is CaCO3. 0.85 Ba 0.15 Cu3Ti 3.97 Hf 0.03 O 12 The content of the auxiliary agent is 0.07wt% based on the total weight of the main components. The preparation method of the auxiliary agent is as follows: 3 mol of copper nitrate trihydrate, 0.85 mol of calcium nitrate tetrahydrate, 3.97 mol of tetrabutyl titanate, 0.3 mol of nitrocitric acid, 0.15 mol of barium nitrate and 0.03 mol of hafnium nitrate are weighed and dissolved in 20L of anhydrous ethanol according to the stoichiometric ratio to obtain a mixed solution, which is kept warm at 83°C for 1.8h, and after adjusting the pH, the mixture is kept warm for reaction until a sol is formed, and then dried, fired and ground to obtain an auxiliary agent powder, wherein the particle size of the auxiliary agent powder is between 0.9-1.1μm.
[0028] A method for preparing a high Curie temperature and high magnetic permeability ferrite, using the above-mentioned high Curie temperature and high magnetic permeability ferrite raw material, comprises the following steps: S31, mixing the main components Fe2O3, ZnO and MnO according to the formula, and then mixing with water in a ratio of 1:1.8, sand grinding and drying for 2.5 hours, and then pre-calcining at a temperature of 830° C. for 1.5 hours in an air atmosphere to obtain a pre-calcined material; S32, mixing auxiliary materials, additives and the pre-burned material obtained in step S31, performing secondary sand grinding and drying to obtain sand-milled powder, the secondary sand grinding time is 2.5 hours; the particle size D50 of the sand-milled powder is 0.8-1.0 μm; S33, the sand-milled powder of step S32 is successively sieved through an 80-mesh sieve, spray-granulated, and a binder is added during the spray-granulation process, wherein the binder is a composition of polyvinyl alcohol and zinc stearate in a mass ratio of 8:1.5, the binder solution concentration is 7wt%, and the binder is 8% of the powder after the sand-milled powder is sieved; forming into a sample ring blank and sintering to obtain a high Curie temperature and high permeability ferrite; the sintering process comprises: heating the sample ring blank to a first temperature of 1050°C at a heating rate of 2.5°C / min, a first insulation time of 5h, introducing a certain amount of oxygen during insulation, under a balanced oxygen partial pressure atmosphere, the oxygen content in the balanced oxygen partial pressure atmosphere is 2.3vol%, cooling to a second temperature of 290°C at a first cooling rate of 4°C / min, a second insulation time of 4h, and finally cooling to a third temperature of 60°C at a second cooling rate of 0.3°C / min.
[0029] Comparative Example 1 The same as Example 3, except that the content of ZnO is changed to ZnO 17.5 mol%.
[0030] Comparative Example 2 The same as Example 3, except that the binder is replaced by a composition of polyvinyl alcohol and zinc stearate in a mass ratio of 8:1.5, with polyvinyl alcohol of equal amount and concentration.
[0031] Comparative Example 3 The same as Example 3, except that the binder is replaced by an equal amount of zinc stearate of the same concentration, which is a composition of polyvinyl alcohol and zinc stearate in a mass ratio of 8:1.5.
[0032] Comparative Example 4 The same as Example 3, except that the content of TiO2 is changed to 0, that is, no TiO2 is added.
[0033] Comparative Example 5 The same as Example 3, except that the content of TiO2 is changed to 0.01wt%.
[0034] Comparative Example 6 The same as Example 3, except that the content of Nb2O is changed to 0, that is, no Nb2O is added.
[0035] Comparative Example 7 The same as Example 3, except that the content of Nb2O is changed to 0.06wt%.
[0036] Comparative Example 8 The same as Example 3, except that the content of the auxiliary agent is changed to 0.012wt%.
[0037] Comparative Example 9 The same as Example 3, except that the content of the auxiliary agent is changed to 0, that is, no auxiliary agent is added.
[0038] Comparative Example 10 The same as Example 3, except that the oxygen content in the equilibrium oxygen partial pressure atmosphere is changed to 1.5 vol%.
[0039] Comparative Example 11 The same as Example 3, except that the first temperature is changed to 1150°C.
[0040] Performance Testing The performance of the high Curie temperature and high magnetic permeability ferrite prepared by Example 1, Example 3 and Comparative Examples 1 to Comparative Examples 11 was tested. The specific testing method was: in accordance with the standard SJ20966-2006 soft ferrite material measurement method, using IWATSUB-H analyzer (SY-8219), the results are shown in Table 1.
[0041] Table 1 As can be seen from Table 1, the high Curie temperature and high permeability ferrite prepared in Examples 1-3 effectively reduces the loss of the high Curie temperature and high permeability ferrite at 100-140°C by controlling the contents of ZnO, TiO2, Nb2O, Co2O3 and additives, optimizing the sintering process to control the temperature and oxygen content, and at the same time ensures the Bs and initial high permeability of the high Curie temperature and high permeability ferrite, so that the loss is as low as 325kW / m under the conditions of 100kHz, 200mT, and 100°C. 3 The loss is as low as 332kW / m under the conditions of 100kHz, 200mT, and 120℃. 3 The loss is as low as 335kW / m under the conditions of 100kHz, 200mT, and 140℃. 3 Below; under the use conditions of 1194A / m, 50Hz, and 100℃, Bs reaches more than 427mT, the initial magnetic permeability reaches more than 12356, and the Curie temperature is between 157-163℃. The high Curie temperature and high magnetic permeability ferrite of the present application is optimized in material composition, process and performance, and has the advantages of low loss, high Curie temperature and high magnetic permeability. It is suitable for high-frequency and high-temperature applications and has great application potential.
[0042] As can be seen from Table 1, from the performance comparison analysis of the high Curie temperature and high magnetic permeability ferrite obtained in Example 3 and Comparative Example 1, the ZnO content is too low and the loss is high.
[0043] As can be seen from Table 1, from the comparative analysis of the performance of the high Curie temperature and high magnetic permeability ferrites obtained in Example 3 and Comparative Examples 2-3, the high Curie temperature and high magnetic permeability ferrites finally obtained by using the binder as a composition of polyvinyl alcohol and zinc stearate in a mass ratio of 8:1.5 have better performance.
[0044] As can be seen from Table 1, from the performance comparison analysis of the high Curie temperature and high magnetic permeability ferrites obtained in Example 3 and Comparative Examples 4-5, when the TiO2 content is too low or too high, the loss trend is not smooth and the loss is also high.
[0045] As can be seen from Table 1, from the performance comparison analysis of the high Curie temperature and high magnetic permeability ferrites obtained in Example 3 and Comparative Examples 6-7, when the Nb2O content is too low or too high, the loss trend is not smooth and the loss is also high.
[0046] As can be seen from Table 1, from the comparative analysis of the performance of the high Curie temperature and high magnetic permeability ferrites obtained in Example 3 and Comparative Examples 8-9, the additive content is too low or too high, and the loss is high.
[0047] As can be seen from Table 1, from the performance comparison analysis of the high Curie temperature and high magnetic permeability ferrite obtained in Example 3 and Comparative Example 10, the oxygen content is relatively low, resulting in high loss and low Bs.
[0048] As can be seen from Table 1, from the performance comparison analysis of the high Curie temperature and high magnetic permeability ferrite obtained in Example 3 and Comparative Example 11, the sintering temperature is too high and the loss is high.
[0049] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A high Curie temperature and high magnetic permeability ferrite, characterized in that: The invention comprises a main component, auxiliary materials and additives. The main component is composed of Fe2O3, ZnO and MnO in molar fraction, with a content of Fe2O3 5253 mol%, ZnO 1819 mol%, and the rest is MnO. The auxiliary materials include CaCO3, ZrO2, Nb2O, Co2O3, SiO2 and TiO2. The auxiliary materials are calculated based on the total weight of the main components, and the content of each auxiliary material component is: CaCO3 0.05-0.07wt%, ZrO2 0.001 0.005wt%, Nb2O 0.025 0.04wt%, Co2O3 0.26 0.28wt%, SiO2 0.004-0.007wt%, TiO2 0.003-0.005wt%. The additive is CaCO3, ZrO2, Nb2O, Co2O3, SiO2 and TiO2. 0.85 Ba 0.15 Cu3Ti 3.97 Hf 0.03 O 12, The auxiliary agent has a content of 0.05-0.08 wt % based on the total weight of the main components.
2. The high Curie temperature and high magnetic permeability ferrite according to claim 1, characterized in that: The preparation method of the auxiliary agent is as follows: copper nitrate trihydrate, calcium nitrate tetrahydrate, tetrabutyl titanate, nitrocitrate, barium nitrate and hafnium nitrate are weighed according to a stoichiometric ratio and dissolved in anhydrous ethanol to obtain a mixed solution, which is kept warm at 83° C. for 1.8 hours, and after adjusting the pH, the mixture is kept warm for reaction until a sol is formed, and then dried, fired and ground to obtain an auxiliary agent powder, wherein the particle size of the auxiliary agent powder is between 0.9 and 1.1 μm.
3. A method for preparing a high Curie temperature and high magnetic permeability ferrite, characterized in that: Using the raw material of the high Curie temperature and high magnetic permeability ferrite according to any one of claims 1-2, comprising the following steps: S31, mixing the main components Fe2O3, ZnO and MnO according to the formula, and then mixing with water in a ratio of 1:1.5-2.0, sand grinding and drying for 2-3 hours, and then pre-calcining at a temperature of 800-850° C. for 1-2 hours in an air atmosphere to obtain a pre-calcined material; S32, mixing auxiliary materials, additives and the pre-burned material obtained in step S31, performing secondary sand grinding and drying to obtain sand-milled powder; S33, the sand-milled powder in step S32 is successively sieved through an 80-mesh screen, spray granulated, molded and sintered to obtain a high Curie temperature and high magnetic permeability ferrite; the molding includes making the product obtained after granulation into a sample ring blank; the sintering process includes: heating the sample ring blank to a first temperature, introducing a certain amount of oxygen during the first insulation, cooling to a second temperature at a first cooling rate under a balanced oxygen partial pressure atmosphere, a second insulation, and finally cooling to a third temperature at a second cooling rate; the first temperature is 1000-1100°C; the second temperature is 270-300°C; the third temperature is 55-65°C.
4. The method for preparing a high Curie temperature and high magnetic permeability ferrite according to claim 3, characterized in that: In step S32, the secondary sand grinding time is 2-3 hours; the particle size D50 of the sand grinding powder is 0.8-1.0 μm.
5. The method for preparing a high Curie temperature and high magnetic permeability ferrite according to claim 3, characterized in that: In step S33, a binder is added during the spray granulation process, wherein the binder is a composition of polyvinyl alcohol and zinc stearate in a mass ratio of 8:1-2.
6. The method for preparing a high Curie temperature and high magnetic permeability ferrite according to claim 5, characterized in that: The concentration of the binder solution is 5-10wt%, and the binder is 6-10% of the powder after the sand-grinded powder is sieved.
7. The method for preparing a high Curie temperature and high magnetic permeability ferrite according to claim 3, characterized in that: In step S33, the heating rate of the heating is 2-3°C / min, and the insulation time at the first temperature is 4-6h.
8. The method for preparing a high Curie temperature and high magnetic permeability ferrite according to claim 3, characterized in that: In step S33, the first cooling rate is 3.5-4.5°C / min, and the second temperature holding time is 3-5h.
9. The method for preparing a high Curie temperature and high magnetic permeability ferrite according to claim 3, characterized in that: In step S33, the second cooling rate is 0.2-0.4°C / min.
10. The method for preparing a high Curie temperature and high magnetic permeability ferrite according to claim 3, characterized in that: In step S33, the oxygen content in the equilibrium oxygen partial pressure atmosphere is 2.12.5 vol%.
Citation Information
Patent Citations
Super high magnetic conductivity, high courier temperature Mn-Zn ferrite and its preparation method
CN101106003A
High-magnetic-permeability manganese-zinc series ferrite and preparation method thereof
CN104387050A
High-performance Mn-Zn ferrite material and preparation method
CN105036726A
Mn-Zn material with wide temperature range, high superposition, high Curie temperature and high permeability and preparation method of Mn-Zn material
CN108610037A
Broadband and five-performance soft magnetic ferrite material and preparation method thereof
CN113327736A